Are Public Sector Workers Different? Cross-European Evidence from Elderly Workers and Retirees - Mirco Tonin; Michael Vlassopoulos (Institute for the Study of Labor (IZA), 2014)
The public sector employs a large share of the labor force to execute important functions (e.g. regulation and public good provision) in an environment beset by severe agency problems. Attracting workers who are motivated to serve the public interest is important to mitigate these problems. We investigate whether public and private sector employees differ in terms of their public service motivation, as measured by their propensity to volunteer, using a representative sample of elderly workers from 12 European countries. To overcome potential identification difficulties related to unobservable differences in working conditions (e.g. working time, required effort, job security, career incentives), we also look at retired workers. We find that public sector workers, both those currently employed and those already retired, are significantly more prosocial; however, the difference in prosociality is explained by differences in the composition of the workforce across the two sectors, in terms of (former) workers' education and occupation. Looking across industries and within occupations, we find that former public sector workers in education are more motivated, while there are no differences across the two sectors when considering broad occupational categories. We also investigate other dimensions and find no differences in terms of trust, while there is evidence of some differences in risk aversion, political preferences, life and job satisfaction.
Keywords: D64; H83; J45; 330; public sector; public service motivation; risk aversion; trust; life satisfaction; volunteering